Principal Leadership Strategies in Revitalizing a High-Synergy Educational Quality Culture - Sitti Nurbani; Fitriati Fitriati; Rahmattullah Rahmattullah (FKIP - Universitas Riau, 2026)
This study aims to analyze principal leadership strategies in revitalizing a high-synergy quality culture in high-performing schools. The research employed a qualitative approach with a comparative case study design conducted at SMP Negeri 1 Peukan Bada, Aceh Besar, and SMP Negeri 2 Banda Aceh City. Data were collected through in-depth interviews, observations, and document analysis involving principals, teachers, administrative staff, and school documents. Data analysis was carried out using descriptive qualitative techniques supported by SWOT analysis, complemented by the Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices. The findings indicate that visionary, participative, and transformational principal leadership plays a crucial role in fostering and sustaining a school quality culture. Internal strengths outweigh existing weaknesses, while external opportunities are greater than potential threats, positioning the schools in the Strength–Opportunity (SO) quadrant. This strategic position suggests that an aggressive and development-oriented strategy is the most appropriate approach. The study concludes that the success of revitalizing a sustainable quality culture is highly dependent on principal leadership that effectively integrates internal capacities and external opportunities in a synergistic manner.